2021
DOI: 10.3390/bs11050058
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of COVID-19 on Work-Related Quality of Life through the Lens of Sexual Orientation

Abstract: In the face of the COVID-19 pandemic and the exceptional situation that has been experienced on a global scale since 2020, it is essential to assess the impact of COVID-19 in several areas and domains. Therefore, this research seeks to evaluate the impact of COVID-19 on work-related quality of life (WRQoL) in a Portuguese-speaking sample, through the lens of sexual orientation. One thousand, five hundred and seventy-seven individuals participated in this study, of which 1396 (88.5%) self-identified as heterose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 79 publications
4
3
0
Order By: Relevance
“…Moreover, the findings of this study also coincide with average quality of working life reported by Easton et al [51]. Mendes and Pereira [52] reported a value of 3.40 in the general Portuguese working population, suggesting that healthcare workers may have lower WRQoL. Pre-pandemic, within the AHPs, one study reported WRQoL scores of 82.92 (14.17) for occupational therapists in Iran [53] while another study of Vietnam's healthcare professionals reported higher scores of 95.52 and 92.10 during the pandemic [54], suggesting that these professionals had higher WRQoL than UK-based respondents.…”
Section: Main Messages In Comparison With the Literaturesupporting
confidence: 91%
“…Moreover, the findings of this study also coincide with average quality of working life reported by Easton et al [51]. Mendes and Pereira [52] reported a value of 3.40 in the general Portuguese working population, suggesting that healthcare workers may have lower WRQoL. Pre-pandemic, within the AHPs, one study reported WRQoL scores of 82.92 (14.17) for occupational therapists in Iran [53] while another study of Vietnam's healthcare professionals reported higher scores of 95.52 and 92.10 during the pandemic [54], suggesting that these professionals had higher WRQoL than UK-based respondents.…”
Section: Main Messages In Comparison With the Literaturesupporting
confidence: 91%
“…These psychosocial circumstances may have increased the existing vulnerabilities of this population. Our study confirms previous data from Portugal and Brazil 70,71 concerning the impact of COVID-19 among LGBTIQ population on mental health and work-related quality of life, and this may have conditioned the access to health care services, through the anticipation of rejection and fear of the disease. On the other hand, the fact that many families do not accept their LGBTIQ family members, led many of our participants to go back into the closet, and this is not without relevant psychosocial consequences, such as LGBTIQ identity erasure on the existing heteronormative culture and exposure to sexual stigma.…”
Section: Change and Copingsupporting
confidence: 90%
“…The mean level of anxiety symptoms in the community samples was 0.93 (SD = 0.73) [40], whereas a mean score of 1.39 (SD = 0.85) was found in our sample. The same trend was observed for occupational well-being indicators: mean levels of work-related quality of life were lower in our sample (3.20; SD = 1.03) than in samples where most participants were straight (3.40; SD = 0.96) [28], work engagement mean scores were lower in our sample (4.12; SD = 1.43) than in samples where the majority of participants were straight (4.65; SD = 1.30), and occupational self-efficacy mean scores in our study were lower (3.31; SD = 0.89) than in samples where the majority of participants were straight (3.66; SD = 0.81) [41]. In addition, we analyzed differences in psychological distress variables (i.e., burnout, depression, and anxiety) and occupational well-being indicators (i.e., WRQoL, work engagement, and occupational self-efficacy) by sexual orientation.…”
Section: A Total Of 305 Portuguese and Braziliansupporting
confidence: 84%
“…During the current coronavirus pandemic, the negative aspects experienced by sexual and gender minorities seem to be even more accentuated, increasing the vulnerabilities of a population that already suffered from previous stressors. Studies carried out in Portugal and Brazil point to higher levels of psychological suffering, depression, anxiety, stress, and fears of losing wages or positions among LGBTQIA+ workers during this period [25][26][27], in addition to a worsening in work-related quality of life and occupational well-being [28]. In a qualitative study with 65 Brazilian and Portuguese LGBTQIA+ people, mental health problems were mentioned 78 times by the participants, and more than a quarter of the sample reported problems at work related to the pandemic context and their LGBTQIA+ identity [29].…”
Section: Introductionmentioning
confidence: 99%